Arboreal ants of Gorgona National Park (Pacific of Colombia) - Chacón de Ulloa, Patricia (2014)
Despite the strong microclimatic fluctuations, scarcity of nesting sites and unpredictable prey availability in open environments, ants are the dominant invertebrates in the tropical forest canopy. This study focused on the arboreal ants in Gorgona National Park, Colombia, a rainforest ecosystem (27ºC, 6 000mm average annual rainfall). In November 2007, 16 trees were sampled by fogging them with a biodegradable pyrethroid insecticide in four levels between 1 and 15 m above the understory vegetation. We found 53 species of Formicidae (24 genera and six subfamilies): two subfamilies had the most species: Formicinae (20 species) and Myrmicinae (17). The most abundant were arboreal species of Azteca, Dolichoderus (D. bispinosus and D. lutosus), Camponotus (C. atriceps, C. claviscapus, C. championi, C. excisus) and Crematogaster (C. brasiliensis, C. carinata, C. curvispinosa). Some species that are common at ground level (Wasmannia auropunctata and Camponotus sericeiventris) were collected up to a height of 15 m. We remark the capture of Nesomyrmex pittieri, Crematogaster stolli, Cephalotes basalis, Anochetus bispinosus and Stigmatomma mystriops, species rarely found using conventional methods. Rev. Biol. Trop. 62 (Suppl. 1): 277-287. Epub 2014 February 01.